PERUBAHAN DAN KONTINUITAS DALAM PEMBUATAN PINISI DI KABUPATEN BULUKUMBA - Sukardi, Aris; Busri, Hasan (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2024)
The research explores changes and continuity in the tradition of building Pinisi boats in Bulukumba Regency, South Sulawesi. The Pinisi boat is a cultural heritage that reflects local innovation in confronting natural challenges and symbolises Indonesia’s maritime cultural identity. The study examines how local communities maintain traditional values while adapting to modern technological and socio-economic conditions through a qualitative descriptive approach. Data were collected through field observations, in-depth interviews with local experts and cultural scholars, and document analysis. The findings show that modern elements have been integrated into the boat-making process, while the ritual essence and traditional values such as communal cooperation, respect for nature, and honouring ancestors are preserved. Local communities combine modern tools with traditional methods at every stage of boat construction, from wood selection to launching into the sea. Sustainable wood resource management is also a primary focus, with practices applied to ensure a continuous supply of raw materials. The research highlights the importance of balancing innovation and tradition to maintain the relevance and sustainability of the Pinisi boat industry. These findings provide insights into how local traditions can adapt to global changes without losing their cultural identity. Additionally, the study contributes to the understanding of the social and cultural dynamics within Pinisi boat-making communities and their role in rural economies and cultural heritage preservation.